Implantación de la contabilidad en Autorepuestos Quingatuña, de la ciudad de Latacunga periodo mayo - junio de 2016 - Armijos Beltrán, Marieta del Pilar (2017)
This thesis work was carried out with the purpose of informing the owner of the ideal way to carry out the accounting based on the application of the International Accounting Standards (IAS). With the implementation of the Accounting, began to fulfill the general objective which was collected the source documentation corresponding to the months of April-May 2016, from which information was collected to control and record the economic activities of the business. Then, the second objective was accomplished: to draw up an initial inventory through the physical verification, to know the assets, values and obligations that the company has and thus to carry out the State of Initial Situation, drawing up a plan and manual Of accounts based on the commercial activity and the needs of the company, for this purpose, accounts are established with their description and respective codification, memorandum of operations, execution of the Daily Book, General Ledger, Check Balance, Worksheet, Income Statement , Statement of Financial Position, Statement of Cash Flows; In order to allow to know the real economic and financial situation of the company. Subsequently, the permanent inventory system was applied using the Weighted Average valuation method. Finally, it is concluded that with the development of this research work, the net profits of the Financial Statements were determined, allowing the owner to make the best decisions for the development and growth of his business. In addition, it is recommended that the business owner continue to use the accounting process, which will enable him to obtain clear and accurate information at any time.